2009
DOI: 10.1038/ajg.2009.80
|View full text |Cite
|
Sign up to set email alerts
|

Association of Proton Pump Inhibitor Therapy With Spontaneous Bacterial Peritonitis in Cirrhotic Patients With Ascites

Abstract: PPI therapy is associated with SBP in patients with advanced cirrhosis. Prospective studies are needed to determine whether PPI avoidance can reduce the incidence of SBP and improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
196
2
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(216 citation statements)
references
References 25 publications
8
196
2
10
Order By: Relevance
“…Among 1141 cirrhotics 446 (39.05%) patients were on proton pump inhibitors where 228 out of 446 on PPI (51.12%) had infections with calculated odd ratio = 2.57 (95% CI 1.99 -3.319) and p value of 0.000. Bajaj JS et al [52] in their study showed that the use of PPI was independently associated with SBP (odds ratio 4.31, confidence interval 1.34 -11.7), and protein within ascitic fluid was found to be protective (OR 0.1, CI 0.03 -0.25). The above study also revealed that 47% of cirrhotic patients receiving PPI had no documented indication for PPI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among 1141 cirrhotics 446 (39.05%) patients were on proton pump inhibitors where 228 out of 446 on PPI (51.12%) had infections with calculated odd ratio = 2.57 (95% CI 1.99 -3.319) and p value of 0.000. Bajaj JS et al [52] in their study showed that the use of PPI was independently associated with SBP (odds ratio 4.31, confidence interval 1.34 -11.7), and protein within ascitic fluid was found to be protective (OR 0.1, CI 0.03 -0.25). The above study also revealed that 47% of cirrhotic patients receiving PPI had no documented indication for PPI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A májelégtelenséget jelző paraméterek (bilirubin>55 µmol/L, thrombocytaszám<98 G/l) az SBP független rizikófaktorainak bizonyultak [31]. Retrospektív esetkontroll-vizsgálatok a protonpumpagátló (PPI-) kezelést hozták összefüggésbe az SBP kialakulásával [34,35]. Az erős savszekréció-gát-lás a gyomorsav antibakteriális hatásának kikapcsolásával a szájon át bekerülő baktériumok túlélését, így a vékony-bélbe jutását segítik, amely miatt nagyobb valószínűség-gel alakul ki SIBO.…”
Section: Az Sbp Hajlamosító Tényezőiunclassified
“…We also attempt to perform swabs seeking for carriage of ESBL-producing strains in patients who are in frequent contact with the health care system and who fulfill the following criteria: on the waiting list, any admission for an acute decompensation of cirrhosis, refractory ascites treated by repeated largevolume paracentesis, use of long-term antibiotic prophylaxis. Since there are ten studies [22][23][24][25][26][27][28][29][30][31] and one metaanalysis [32] showing that the use of proton-pump inhibitors increases the risk of developing SBP, PPI administration should not be recommended, at least in patients with ascites.…”
mentioning
confidence: 99%